An Effect of Via-Holes Barriers on Circularly Polarized Patch Antennas for Getting Currents' Phase-Lags - Matsunaga, Mayumi (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2018)
A simple way to get 90 degrees currents' phase-lags on patch antennas is presented in this paper. Structures to get 90 degrees currents' phase-lags are necessary for constituting circularly polarized (CP) antennas. In this study, via-holes barriers are made for making the currents' phase-lag on patch antennas. The effect of the via-holes barriers on a square path antenna is explained first. Then, the via-holes barriers have been applied to constitute a CP patch antenna. The CP antenna is constituted to the size of 0.17µ×0.15µ (µ is the free space wave length) due to the via-holes barriers.